[Ribbon cutting for Caroni's (1975) Limited's aquaculture project] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Formal cutting of the ribbon for Caroni Limited's Aquaculture Project by A.N.R. Robinson. On Mr. Robinson's right is Winston Dookeran, who was Minister of Research and Development and on the left, Deputy Chairman of Caroni's Board, Dr. Rajitsingh.
Cataloger's title
Keywords: Dedication services -- Trinidad and Tobago; Caroni (1975) Limited -- Rites and ceremonies; Caroni (1975) Limited